Pengaruh Penerapan PSAK 45 dan Ketepatwaktuan Penyampaian Laporan Keuangan terhadap Akuntabilitas Laporan Keuangan Organisasi Nirlaba - Olivia Lungit Astari Putri; Sri Ayem (Owner : Riset dan Jurnal Akuntansi, 2021)
Non-profit organizations/institutions need to comply with regulations in managing financial reports. The purpose of this study was to examine the impact of using PSAK No. 45 and timely submission of financial reports to accountability for these financial statements. The population used is the Yogyakarta Special Region Social Foundation. Sampling using purposive sampling. This research is quantitative with primary data in the form of questionnaires and multiple linear regression analysis methods to test hypotheses. The results found in this study are the application of PSAK No. 45 partially have a positive and significant impact on the accountability of financial statements, and the timeliness of the submission of financial statements partially has a positive and significant impact on the accountability of financial statements. In addition, the application of PSAK No. 45 and the timely submission of financial reports simultaneously or simultaneously also affects the accountability of financial statements by 43.7%. So, every non-profit organization must apply accounting standards in its financial statements and these financial statements must be submitted in a timely manner to be accountable. This study applies compliance theory to prove the research results and support the authors' ideas.